Rearing performance of Merino, South African Mutton Merino and Dormer ewes in relation to live mass, reproduction and pelvic dimensions - Cloete, S.W.P. (1994)
Live mass reproduction and pelvic dimensions (determined mainly by radiographic pelvimetry at more than 4 years of age) were obtained for ewes of the Langgewens Merino flock (n=102), ewes of the Tygerhoek Merino flock (n=434) and ewes of the Elsenburg South African Mutton Merino (n=130) and Dormer flocks (n=130). Ewes were classified as "good" or "poor" according to their rearing ability (ewes rearing/ewes lambed-Er/El) and rearing performance (lambs reared/lambs born -Lr/Lb) averaged over at least 4 lambings in 4 to 5 lambing opportunities. Good ewes tended to be lighter than poor ewes at 18 months (Merino) or weaning (South African Mutton Merino and Dormer). This tendency was also reflected in live mass at the time of radiography, being significant (P